Enhancing Logistics Distribution Efficiency for Indonesian Navy Warships in Operations Area - Aris Sarjito (West Science Interdisciplinary Studies, 2024)
The Indonesian Navy faces challenges in maintaining the readiness of warships deployed in external operation areas due to inefficiencies in logistics distribution. Understanding current practices and identifying bottlenecks is crucial for devising strategies to enhance logistics efficiency. This study aims to investigate the current logistics distribution practices of the Indonesian Navy, identify primary bottlenecks and inefficiencies, explore opportunities for optimization, and propose strategies for increasing logistics distribution efficiency to support warships in external operation areas. Utilizing Creswell's qualitative research framework, this study analyzes existing secondary data from academic journals, reports, and governmental documents related to naval logistics in Indonesia. The study reveals the current logistics distribution practices and procedures of the Indonesian Navy, identifies primary bottlenecks and inefficiencies within the existing system, explores opportunities for optimization of logistics processes and infrastructure, and proposes a comprehensive strategy for increasing logistics distribution efficiency to support the readiness of Indonesian Navy warships in external operation areas. By leveraging qualitative research methods and secondary data analysis, this study provides valuable insights into enhancing logistics distribution efficiency for Indonesian Navy warships, contributing to improved readiness and operational effectiveness in external operation areas.